PEMANFAATAN CLAY EX. BENGALON SEBAGAI AGREGAT KASAR BUATAN DAN PASIR EX. TENGGARONG DALAM CAMPURAN BETON DENGAN METODE STANDAR NASIONAL INDONESIA 03-2847-2002 - Ridwan, Mochamad (KURVA S JURNAL MAHASISWA, 2014)
This study uses a method of designing the concrete mix of Indonesian National Standard 03-2847-2002. That is done in the laboratory using artificial coarse aggregate size is the size of coarse aggregate-made by using the middle limit and random. The sample used for each of the artificial coarse aggregate size amounted to 30 samples.Results of all testing that the clay ex. Bengalon has a fairly high abrasion value is 60.08% in aggregate categories that can not be used as coarse aggregate for concrete structural class II, and the quality of K-125, K-175 and K-225 with abrasion condition (27-40%) , a very high absorption values ranging from 20.223% to control water demand in concrete mix is relatively difficult, and low yields an average compressive strength of 28 days is generated based on the Indonesian National Standard 03-2847-2002 method for coarse aggregate size limit of the middle and random namely 10.372 MPa and 10.089 MPa of compressive strength of concrete were targeted (f'cr) = 25.7 MPa. Keywords: Design Mix Concrete SNI 03-2847-2002, Clay ex. Bengalon, Sand ex. Tenggarong, Concrete